The Maroons of Prospect Bluff and Their Quest for Freedom in the Atlantic World - Millett, Nathaniel (Book collections on Project MUSE., 2013)
In this book, the author examines how the Prospect Bluff maroons constructed their freedom, shedding light on the extent to which they could fight physically and intellectually to claim their rights. The author considers the legacy of the Haitian Revolution, the growing influence of abolitionism, and the period's changing interpretations of race, freedom, and citizenship among whites, Blacks, and Native Americans. -- Resource home page.